16
Пошаговое объяснение:
(2023 - 2576 : х) * 7 = 13034
2023 - 2576 : х = 13034 : 7
2023 - 2576 : х = 1862
2576 : х = 2023 - 1862
2576 : х = 161
х = 2576 : 161
х = 16
(2023 - 2576 ÷ х) × 7 = 13034
2023 - 2576 ÷ х = 13034 ÷ 7
2023 - 2576 ÷ х = 1862
2576 ÷ х = 2023 - 1862
2576 ÷ х = 161
х = 2576 ÷ 161
16
Пошаговое объяснение:
(2023 - 2576 : х) * 7 = 13034
2023 - 2576 : х = 13034 : 7
2023 - 2576 : х = 1862
2576 : х = 2023 - 1862
2576 : х = 161
х = 2576 : 161
х = 16
(2023 - 2576 ÷ х) × 7 = 13034
2023 - 2576 ÷ х = 13034 ÷ 7
2023 - 2576 ÷ х = 1862
2576 ÷ х = 2023 - 1862
2576 ÷ х = 161
х = 2576 ÷ 161
х = 16